Geology of Batu Gajah with Emphasis on the Characteristics of Carbonaceous Schist for Hydrocarbon Prediction - Ong, Ching Yee (2016)
Five samples from the Palaeozoic carbonaceous schist outcrops were collected in Batu Gajah for Scanning Electron Microscope (SEM), Energy-dispersive X-ray spectroscopy (EDX) and Total Organic Carbon (TOC). The analysis of these carbonaceous schist samples intends to determine the characteristic and organic matter amount across the Palaeozoic boundary contained in the rocks for hydrocarbon prediction. The Palaeozoic carbonaceous schist outcrops in Batu Gajah were selected to conduct detail analysis after micro-paleontological characterization and datation by other researchers. The Palaeozoic carbonaceous rocks in the form of graphitic schists are the deep marine deposit found in Batu Gajah area, which is part of the Kledang Range located in the western belt of Peninsular Malaysia. Carbonaceous schist discovered in Batu Gajah was formed from black shale by regional metamorphism. This is manifested by the intrusion of Kledang Range granite in the Mesozoic age. Carbonaceous shales have always been associated with their prominent potential as a hydrocarbon source rock. As the shale is heated above the oil and gas window, its organic matter constituents are transformed to graphite. Five carbonaceous schist samples from Batu Gajah were analyzed. Four out of five samples showed very low Total Organic Carbon (TOC) values. However, one sample contains about 2.54 wt % of TOC and thus, this sample contains mature organic matter.